Ethical problems in emergency medicine : a discussion-based review - Jesus, John. (Hoboken, N.J. : Wiley-Blackwell, 2012)
This book is designed to consolidate the relevant literature as well as the thoughts of professionals currently working in the field into a practical and accessible reference for the emergency medical technician, student, nurse, resident, and attending emergency physician. Each chapter is divided into four sections: case presentation, discussion, review of the current literature, and recommendations. Designed to serve simultaneously as a learning and reference tool, each chapter begins with a real case that was encountered in an ED setting. The case presentation is followed by a short discussion.
Ethical Problems in Emergency Medicine; Contents; Contributors; Preface; Section One: Challenging professionalism; 1: Physician care of family, friends, or colleagues; 2: The impaired physician; 3: Disclosure of medical error and truth telling; 4: Conflicts between patient requests and physician obligations; 5: Judgmental attitudes and opinions in the emergency department; 6: Using physicians as agents of the state; Section Two: End-of-life decisions; 7: Family-witnessed resuscitation in the emergency department: making sense of ethical and practical considerations in an emotional debate.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Emergency medicine -- Moral and ethical aspects; Medical ethics; MEDICAL -- Ethics; Emergency medicine -- Moral and ethical aspects; Medical ethics; Emergency medicine - Moral and ethical aspects; Emergency medicine -- Moral and ethical aspects; Medical ethics; Electronic books; Electronic books; Electronic books